A perspective on polythiophenes as conformation dependent optical reporters for label-free bioanalytics - Sinsinbar, Gaurav (2022)
Poly(3-alkylthiophene) (PT)-based conjugated polyelectrolytes (CPEs) constitute an important class of responsive polymers with excellent optical properties. The electrostatic interactions between PTs and target analytes trigger complexation and concomitant conformational changes of the PT backbones that produce distinct optical responses. These conformation-induced optical responses of the PTs enable them to be utilized as reporters for detection of various analytes by employing simple UV-vis spectrophotometry or the naked eye. Numerous PTs with unique pendant groups have been synthesized to tailor their interactions with analytes such as nucleotides, ions, surfactants, proteins, and bacterial and viral pathogens. In this perspective, we discuss PT-target analyte complexation for bioanalytical applications and highlight recent advancements in point-of-care and field deployable assays. Subsequently, we highlight a few areas of critical importance for future applications of PTs as reporters, including (i) design and synthesis of specific PTs to advance the understanding of the mechanisms of interaction with target analytes, (ii) using arrays of PTs and linear discriminant analysis for selective and specific detection of target analytes, (iii) translation of conventional homogeneous solution-based assays into heterogeneous membrane-based assay formats, and finally (iv) the potential of using PT as an alternative to conjugated polymer nanoparticles and dots in bioimaging.